Community perceptions and home management of malaria in selected rural communities of Ogun state, Nigeria (2013)
Home Management of Malaria (HMM) is a component of the roll back malaria (RBM) programme being implemented for over a decade to reduce the malaria burden. This study examined the extent to which HMM has raised the ability in promptly recognising and treating malaria at home. This was a descriptive cross-sectional study of 262 pregnant women attending antenatal clinics and 233 mothers of under-five children using semi-structured questionnaire in Ijebu North and Yewa North local government areas of Ogun State. Data collection also involved focus group discussions. Quantitative and qualitative data were analysed using EpiInfo 6.04a and Textbase Beta softwares respectively. Only 32.7% of respondents knew about HMM. About 48% preferred analgesics unlike ACTs (0.6%) for malaria treatment. While 45.5% (61.1% Yewa North vs. 29.2% Ijebu North) knew LLIN, only 23.6% used it. Lack of awareness was the major reason for non-use of ACTs (86.1%) and LLINs (71.3%) in HMM. Locality, age, and education significantly determined awareness and use of ACTs and LLIN (p<0.05). Adequate information and stock of ACTs and LLINs should be made available and accessible for the RBM and MDG targets to be realised in the study communities.